Effects of bruxism on the maximum bite force - Todić, Jelena T; Mitić, Ankica; Lazić, Dragoslav; Radosavljević, Radivoje; Radosavljević, Radivoje; Staletović, Miloš (Vojnosanitetski pregled, 2017)
Background/Aim. Bruxism is a parafunctional activity of the masticatory system, which is characterized by clenching or grinding of teeth. The purpose of this study was to determine whether the presence of bruxism has impact on maximum bite force, with particular reference to the potential impact of gender on bite force values. Methods. This study included two groups of subjects: without and with bruxism. The presence of bruxism in the subjects was registered using a specific clinical questionnaire on bruxism and physical examination. The subjects from both groups were submitted to the procedure of measuring the maximum bite pressure and occlusal contact area using a single-sheet pressure-sensitive films (Fuji Prescale MS and HS Film). Maximal bite force was obtained by multiplying maximal bite pressure and occlusal contact area values. Results. The average values of maximal bite force were significantly higher in the subjects with bruxism compared to those without bruxism (p < 0.001). Occlusal contact area was significantly higher in the subjects suffering from bruxism (p < 0.001), while the maximal bite pressure values did not show a significant difference between the studied groups (p > 0.01). Maximal bite force was significantly higher in the males compared to the females in all segments of the research. Conclusion. The presence of bruxism influences the increase in the maximum bite force as shown in this study. Gender is a significant determinant of bite force. Registration of maximum bite force can be used in diagnosing and analysing pathophysiological events during bruxism.
Keywords: bruxism; bite force; dental occlusion; sex; male; female